2022
DOI: 10.1186/s12911-022-01898-3
|View full text |Cite
|
Sign up to set email alerts
|

Data quality and associated factors in the health management information system at health centers in Shashogo district, Hadiya zone, southern Ethiopia, 2021

Abstract: Background Poor quality routine data contributes to poor decision-making, inefficient resource allocation, loss of confidence in the health system, and may threaten the validity of impact evaluations. For several reasons in most developing countries, the routine health information systems in those countries are described as ineffective. Hence, the aim of this study is to determine the quality of data and associated factors in the routine health management information system in health centers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Our study revealed that supportive supervision by higher-level officials is another significant factor linked to the good completeness of data in institutional birth. This finding is consistent with prior studies conducted in Ethiopia and Indonesia [ 65 , 66 ], which highlighted the effectiveness of supportive supervision in improving health care data quality. Therefore, Policymakers, program managers, and officials at the district and higher administrative levels need to prioritize strengthening regular supervision and directives for healthcare facilities, enabling healthcare providers to promptly identify and correct data quality gaps in the services they deliver [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study revealed that supportive supervision by higher-level officials is another significant factor linked to the good completeness of data in institutional birth. This finding is consistent with prior studies conducted in Ethiopia and Indonesia [ 65 , 66 ], which highlighted the effectiveness of supportive supervision in improving health care data quality. Therefore, Policymakers, program managers, and officials at the district and higher administrative levels need to prioritize strengthening regular supervision and directives for healthcare facilities, enabling healthcare providers to promptly identify and correct data quality gaps in the services they deliver [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, conducting RCA to address identified data quality gaps was found to have a positive association with the good consistency of institutional birth data.Prior studies have reported the effectiveness of routine data quality evaluation methods like LQAS in ensuring the quality of RHIS data [ 62 , 65 ]. In our study, although LQAS performance was uniform across health facilities, differences in RCA practice demonstrated its importance in improving the data quality across IMRs in institutional birth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in previous studies conducted in Senegal, 6 Rwanda, 7 Mozambique, 8 and Ethiopia, 9 suggesting that data quality issues are prevalent in malaria reporting systems across different countries. These studies highlight discrepancies in data accuracy, completeness, and timeliness, as well as the availability of written guidelines, standardized registers, and reporting forms.…”
Section: Discussionsupporting
confidence: 89%
“…Even though Ethiopia has made impressive progress in the utilization of HIS in recent years, a growing body of evidence indicates that the level of data quality and the use of information for decision-making is still not adequate, which in turn affects the level of HMIS implementation. 12 , 16 , 17 In addition, to the best of the author’s knowledge, no research has been conducted on the level of DHIS2 implementation in the public HFs in the study setting. As a result, this study aimed to assess the level of DHSI2 implementation among public HFs in Dire Dawa City Administration.…”
Section: Introductionmentioning
confidence: 99%